Development and validation of Science Instructional Materials (SIMs) for the least learned competencies - Macalikod, Rakma; Simpal, Ebrahim Alpe (Goodwood Publishing, 2025)
Purpose: This study focused on developing and evaluating Science Instructional Materials (SIMs) to address the least-learned competencies among Grade 8 students, providing structured resources for learners struggling with key scientific concepts. Research methodology: A research and development approach was employed, identifying the least learned competencies through summative assessments. The SIMs were designed based on these competencies and evaluated by science teachers, master teachers, and Learning Resource Management and Development System (LRMDS) members. The evaluation criteria included content quality, format, presentation, organization, and accuracy, with statistical analysis to examine differences in ratings. Results: The SIMs received high ratings across all evaluation categories, with no significant differences in the assessments from science teachers, Master Teachers, and LRMDS members, indicating broad acceptance and reliability. Conclusions: The findings showed that SIMs were highly rated, aligning well with instructional standards and classroom needs. While there were significant differences in ratings among evaluator groups, the overall acceptability was high, suggesting that the SIMs effectively addressed learning challenges, particularly in physics. Their structure, clarity, and adherence to curriculum standards were affirmed. Further validation is required in diverse educational contexts. Limitations: This study was limited to a single public secondary school, which may affect the generalizability of the findings. Additional validation in various educational settings is needed. Contribution: This study provides an evidence-based approach for developing instructional materials in science education, focusing on addressing learning gaps and supporting competency development. Novelty: This study introduces SIMs specifically designed to enhance competencies identified as least learned, validated through expert evaluation aligned with curriculum standards.